Epimicrobiome Shifts With Bleaching Disease Progression in the Brown Seaweed Saccharina japonica - Ling, Fan; Egan, Suhelen; Zhuang, Yingrui; Chang, Lirong; Xiao, Luyang; Yang, Qin; Wang, Gaoge (Frontiers in Marine Science, 2022)
Recent bacterial induced bleaching disease events of the commercially farmed brown seaweed Saccharina japonica has resulted in significant reduction in healthy sporeling supply. However, to date the host associated epimicrobial community shifts with the disease progression have not been characterized. We investigated the dynamic shifts in the composition of the epibacterial communities of S. japonica with disease progression using 16S rRNA gene amplicon sequencing. We found that the alpha diversity was significantly higher in the control group than in the infected group over disease progression (P < 0.01). There was a significant shift in the composition and predicted functions of the epibacterial communities in both control and infected groups. Indicator species, belonging to Stenotrophomonas, Pseudomonas and Sphingomona were significantly higher in the control group than infected group, suggesting that these taxa are associated with healthy S. japonica. In contrast, Vibrio, Pseudoalteromonas and Colwellia were keystone taxa in the infected group at 24 h, and thus maybe considered to be the secondary opportunistic pathogens. Our study describes the changes of epibacterial communities associated with the progression of bleaching disease in S. japonica. This new information not only extends our baseline knowledge of the S. japonica epimicrobiome, but also paves the way for developing measures to mitigate disease outbreaks for the sustainable aquaculture of S. japonica.